Population genetic analysis of a parasitic mycovirus to infer the invasion history of its fungal host - Schoebel, Corine N; Botella, Leticia; Lygis, Vaidotas; Rigling, Daniel (Molecular ecology, 2017)
Hymenoscyphus fraxineus mitovirus 1 (HfMV1) occurs in the fungus Hymenoscyphus fraxineus, an introduced plant pathogen responsible for the devastating ash dieback epidemic in Europe. Here, we explored the prevalence and genetic structure of HfMV1 to elucidate the invasion history of both the virus and the fungal host. A total of 1298 H. fraxineus isolates (181 from Japan and 1117 from Europe) were screened for the presence of this RNA virus and 301 virus-positive isolates subjected to partial sequence analysis of the viral RNA polymerase gene. Our results indicate a high mean prevalence (78.7%) of HfMV1 across European H. fraxineus isolates, which is supported by the observed high transmission rate (average 83.8%) of the mitovirus into sexual spores of its host. In accordance with an expected founder effect in the introduced population in Europe, only 1.1% of the Japanese isolates were tested virus positive. In Europe, HfMV1 shows low nucleotide diversity but a high number of haplotypes, which seem to be subject to strong purifying selection. Phylogenetic and clustering analysis detected two genetically distinct HfMV1 groups, both present throughout Europe. This pattern supports the hypothesis that only two (mitovirus-carrying) H. fraxineus individuals were introduced into Europe as previously suggested from the bi-allelic nature of the fungus. Moreover, our data points to reciprocal mating events between the two introduced individuals, which presumably initiated the ash dieback epidemic in Europe.
Keywords: Genetics, Population; genetická variace; Ascomycota; fylogeneze; Genetic Variation; Japan; populační genetika; Phylogeny; Europe; mykoviry; Fungal Viruses; Evropa; nemoci rostlin; Plant Diseases; Japonsko; Fraxinus